Assessment and Control of Noise Pollution in Seal Gas Compressor of Reduction Unit 2 of a Steel Industry - Gholam Abbas Shirali; Sanaz Karimpour; Davod Afshari (Salāmat-i kār-i Īrān, 2019)
Background and aims: Undoubtedly, noise and vibration are major problems of industrial world and lot of people are very exposed to these phenomena in their workplace or residential areas. Researchers have shown that exposure to noise may increase the risks related to personal health, like nervous frailty, extreme irritability, muscle cramps, stress and anxiety, dizziness, headache and migraine, anger, loss of body balance, vomiting, pain, hypertension, high blood pressure, cardiovascular problems, deterioration of sleep quality, mental stress, etc. However, the purpose of this study was to assess and control and reduce the risks resulting from noise in the reduction unit 2 of a steel industry. Methods: This study was conducted in two steps. 1) Evaluation of noise pollution in the compressor room and its surrounding: For this purpose, total sound pressure level (SPL) and SPLpeak were measured in the places where workers worked or were traveled. The parameters were measured in the mentioned places according to a grid pattern in both the compressor turn on/off. Because the workers exposed to a noise fluctuating, in addition to SPL analysis on the octave-band frequencies to determine critical frequency when the compressor was switched on, the value of Leq was also measured. The critical frequency is very important in noise control issues. The measurements were performed by using sound level meter, model of “B&K 2231.” The apparatus was calibrated before and after measurements by using “B&K 4230 calibrator.” 2) Noise control measurements: After identifying noise leakage paths to outside of the compressor room, noise was controlled in door, wall-fans and roof window area through installing a silencer on the wall-fans and redesigning the door and the roof window using the previous step data. Results: Inside the compressor room, the total sound pressure level and the critical frequency was estimated 106.2 dB (A) and of 250 Hz in the Lin network, respectively. The total sound pressure level in the area around the compressor and the critical frequency were also estimated 94.3 dB (A) and 2000 Hz respectively. Moreover, the value of Leq was more than the threshold value (<85 dB) at all measured stations. In order to control the noise in the area of ​​the fans, considering the noise assessment and the critical frequency, there was used an absorption silencer with glass wool as adsorbent material. To control noise at the door and roof window, there was designed and installed a steel door with dimensions of 3.9 * 2.13 meter and thickness of 1.5 mm which was filled by a noise-adsorbent 40 mm of glass wool and attached to a metal grid. Moreover, to control noise in the roof window was applied a structure with the same specifications, but with the different dimensions (4.2 * 4.2 m and 7 mm mesh diameter). However, the results related to before and after implementation of the control measurements showed an acceptable attenuation in the SPL (91.8%). The average SPL before and after implementation of the control measurements was 95 and 87.2 dBA, respectively which this value was an acceptable level in comparison with background noise, i.e., 86.4 dBA. On the other hand, The slight difference between the mean value of the background sound pressure level and the average of controlled sound pressure level (0.8 dB) is due to factors such as temperature, variations in sound at different positions, generated noise sources (off or on and so no) and the movement of fluids in the pipes and so on.